Integration of Human Resource Management and Leadership Culture in Corporate Social Responsibility - Mulya, Fitra (Ilomata International Journal of Social Science, 2025)
This study explores the integration of Human Resource Management (HRM) and leadership culture within Corporate Social Responsibility (CSR) frameworks. Using a qualitative research approach based on a literature review, the article examines how HRM strategies and leadership values intersect to enhance CSR initiatives in organizations. By reviewing relevant academic literature and case studies, the research identifies key themes such as the role of leadership in fostering CSR values, the alignment of HR practices with social responsibility goals, and the impact of leadership culture on employee engagement in CSR activities. The findings suggest that successfully integrating HRM and leadership culture into CSR practices improves organisational reputation, enhances employee morale, and strengthens stakeholder relationships. The study highlights the importance of leadership in setting ethical standards and ensuring that CSR objectives are embedded within the organisation's strategic goals. HRM practices, such as talent development, employee engagement, and ethical performance evaluations, promote a culture of responsibility and sustainability. The article contributes to ongoing discussions about the strategic role of HRM and leadership in CSR, offering insights for companies seeking to strengthen their commitment to sustainable and socially responsible business practices.